3D analysis of player's movement during the volleyball match - Zahalka F.; Maly T.; Hank M. (13th International Symposium on the 3D Analysis of Human Movement, 14-17 July, 2014, Lausanne, Switzerland, 2014)
The aim of this study was to reconstruct the three-dimensional position and movement of players in volleyball match. Subsequently to evaluate and quantify the total amount of player movement in terms of player positions in the volleyball court and compare the level of external load of the individual players` positions during the match. External load was estimated by volume of absolute distance traveled on the field and individual playing time. Match was recorded by using four HD camcorders. Each pair panned one half of playing field, which was calibrated using calibration blocks of dimensions 9x9x2 m. 3D reconstruction was processed by software TEMA Bio2.3 using the DLT (Direct linear transformation) algorithm method. Match for analysis was selected from the highest European women`s competition in which the movement was evaluated for a total amount of 14 female players played in 4 sets. During the match the average movement distance of players in horizontal plane was 1259 m. The shortest distance performed was by players at middle blocker position with an average of 872 m. The rest of players` positions have undergone a comparable distance of 1453 m. All values must be assessed according to the time spent on the field. The average minimum distance for a single rally was 1.05 m and maximum was 30.6 m.